Inconsistent use of condom: risky sexual behaviour among the street based sex workers in Kathmandu Valley - Karki, Rita (Nepal Population Journal, 2018)
The nature of profession of sex trade is multi partnered which leads the sex partners to unprotected sex. This study aims to explore the knowledge and experiences of STIs, practice and use of condom, reasons of not using it regularly and addiction situations among the street based female sex workers (SFSWs) in Kathmandu Valley. This study is a non-experimental research based on cross-sectional design. Mixed method was used to collect information with 110 SFSWs selected by using snow ball sampling techniques and presented descriptively after arranging in different themes. Among the SFSWs, 64.5 percent experienced STIs and 69 percent of them were unable to use condoms regularly. Most of the sex workers agree to unprotected sex when they are offered extra money and forced for sex by clients without condom, and another reason was lack of skill on SFSWs in using it properly. Knowingly or unknowingly SFSWs, clients and their life-partners are being victimized from practicing of risky sexual behaviour. The study suggests that touchy and broad awareness programs and compulsory rule to use male condom from clients’ side within safer indoor work space could be effective in helping to assure satisfying and safe sex.